Avifauna Di Desa Makmur Jaya, Kecamatan Tikke Raya, Kabupaten Pasangkayu, Provinsi Sulawesi Barat - Rahayu, Slamet Mardiyanto (Universitas Muhammadiyah Surakarta, 2019)
Biodiversity is a component that is sensitive to changes in land use. Birds are an avifauna found in almost every place and have an important position as one of Indonesia's animal wealth. The high level of biodiversity is not supported by data and information about its distribution, the taxonomy is still limited and not well documented. Based on this, it is necessary to explore the distribution of birds in various regions, so that they can be collected in a database to support the bioconservation program. Therefore, this research needs to be done to determine the type of avifauna in Makmur Jaya Village, Tikke Raya District, Pasangkayu Regency, West Sulawesi Province. The research was in the form of exploration by observing and recording the species of birds found. Based on the research found 23 types of avifauna in Makmur Jaya Village, Tikke Raya District, Pasangkayu Regency, West Sulawesi Province, namely: Alcedo atthis, Aythya australis, Rhyticeros cassidix, Chalcophaps stephani, Streptopelia chinensis, Macropygia amboinensis albicapilla, Corvus enca, Turacoena manadensis, Phaenicophaeus calyorhynchus, Dicrurus hottentottus, Todiramphus chloris, Hirundo tahitica, Aethopyga siparaja, Nectarinia jugularis, Passer montanus, Gallus gallus, Loriculus stigmatus, Pycnonotus aurigaster, Gallirallus torquatus, Ninox punctulata, Phylloscopus sarasinorum, and Bubulbus ibis.